Promoting the Indonesian Special Economic Zones for Tourism: Lessons from Mandalika and Tanjung Kelayang - Adam, Latif (Economics and Finance in Indonesia, 2019)
This paper aims to analyze the design and implementation of the policy to develop tourism special economic zones (TSEZs) in Indonesia with special reference to Mandalika and Tanjung Kelayang. Using descriptive analysis, it is revealed that these TSEZs have not attracted many investors yet. The policy design to promote the two TSEZs is unattractive, unclear, and at odds with the characteristics of the tourism sector. Furthermore, the implementing institutions have insufficient capacity and professionalism to implement the policy. Various critical actions are necessary to take. First, accelerating the provision of infrastructure. Second, clarifying several regulations to be in compliance with the characteristics of the tourism sector. Third, improving the capacity of the implementing institutions to manage the TSEZs. Fourth, encouraging both TSEZ Managements to collaborate.